The negative impact of wind turbines on wildlife in South Africa - Docrat, Nadeemah (My University, 2023)
Wind energy has an exponential growth rate across the world and is seen as the most efficient and reliable source of renewable and green energy technology. However, its negative impacts include the destruction of wildlife habitats and ecosystems and are the cause of many birdlife fatalities. National environmental legislation and assessments provide the basis on which environmental protection and conservation are achieved and as such will be reviewed to identify the level to which avian protection against wind turbines is ensured. This research report aims to investigate the relationships that exist between wind turbines and their subsequent negative effects on avifauna mortality and to understand if environmental legislation reduces the negative impacts caused by wind turbines on avifauna. This is done in the case study area of South Africa and the Western Cape province. Qualitative, exploratory methods will be used in the collection of secondary data. Through the identification of three diurnal raptors most affected by wind turbines in the Western Cape and through the review of two wind farms EIA reports in the Western Cape province, it is evident that wind turbines do negatively affect avian species and contribute to their mortality. Furthermore, whilst environmental legislation underpins the protection and conservation of the natural environment in the country, environmental assessments have the most important role in ensuring the protection of avians and wildlife against the negative impacts that wind turbines present.
A dissertation submitted in fulfillment of the requirements for the degree of Master of Urban Studies to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, 2023